Peningkatan hasil belajar siswa sekolah dasar menggunakan media kertas bergambar pada materi perkembangbiakan tumbuhan tema 1 - Enin Iriani (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2019)
Student learning outcomes on plant propagation material need to be improved. That is because the material is difficult and needs media to help to learn. The purpose of this research is to improve student learning outcomes at primary school level using paper media display on plant propagation material. The method used is Classroom Action Research with three cycles. The study was conducted on July 2019. The instrument used was a matter of learning achievement test in the form of a description item. The results showed that student learning outcomes increased after using illustrated paper on plant breeding material, even though the increase in learning outcomes was included in the low category (N-gain < 0.3). The conclusion of this research is an increase in student learning outcomes in plant breeding material using pictorial paper media.